Organic matter, water infiltration and tomographic images of Latosol in reclamation under different managements - Marchini, Debora C. [UNESP]; Ling, Tseng C.; Alves, Marlene C. [UNESP]; Crestana, Silvio; Souto Filho, Sebastiao N. [UNESP]; Arruda, Otton G. de [UNESP] (Univ Federal Campina Grande, 2015)
In this study the objective was to evaluate the effects of different managements on reclamation of an Oxisol for seven years. The treatments were: two controls, A - Savannah vegetation; B - exposed soil; besides the treatment, C - Area with only tree species Astronium fraxinifolium (GA); D - A. fraxinifolium + Raphanus sativus until 2005, replaced by the following Crotalaria juncea (GA + C); E - A. fraxinifolium + Canavalia ensiformis (GA + FP); F - A. fraxinifolium+sewage sludge + Brachiaria decumbens (GA + LE + B). There was no convergence with respect to the behavior of soil quality indicator in recovery for seven years, studied in this work; treatment A. fraxinifolium+sewage sludge + Brachiaria decumbens provided the best response to soil organic matter content; the treatments used for soil reclamation had similar water infiltration; the treatments with A. fraxinifolium + Crotalaria juncea; A. fraxinifolium+Canavalia ensiformis and A. fraxinifolium + sewage sludge + Brachiaria decumbens in soil tomographic images were those with the best conditions of soil structure, the recovery process has reached the soil layer of 0-10 cm.
Keywords: soil microtomography; soil structure; sewage sludge; green manure